Examining the Constitutionality of the Minister of Home Affairs’ Appointment of Acting Governors, Regents, and Mayors During the 2024 Regional Election Transition - Makiin, Inda Dzil Arsyi; Alamsyah, Mirah Satria; Ja'far, A. Kumedi (As-Siyasi: Journal of Constitutional Law, 2024)
Law Number 10 of 2016 concerning Regional Head Elections (UU Pilkada) mandates the implementation of Simultaneous Regional Head Elections in 2024. As this event approaches, many regional heads will complete their terms before the elections, leading to vacancies filled by Acting Regional Heads (Pj). These appointments, lasting up to 2.5 to 3 years, have occurred without technical regulations, with 103 appointments made as of January 20, 2023, raising controversies and procedural issues. This research aims to examine the constitutional conformity of the appointment process, the potential for conflicts of interest in the appointment and placement of acting regional heads, and the application of meritocracy in these appointments. The study employs a normative legal approach using secondary data consisting of primary and secondary legal materials. The findings indicate that the appointment of acting regional heads is not in accordance with the Constitution due to insufficient public participation, as mandated by Constitutional Court Decision Number 91/PUU-XVIII/2020. Furthermore, there is a lack of information transparency, violating Article 28F of the Constitution. The study also highlights the potential for conflicts of interest in the appointment and placement processes, posing significant risks to public integrity and trust. Additionally, the application of meritocracy in appointing acting regional heads, particularly those with military or police backgrounds, is considered justifiable due to their expertise in institutional management gained through professional experience and education.